The stellar content of the young open cluster Trumpler 371. Issue 7 (1st August 2013) - Errmann, R.; Neuhäuser, R.; Marschall, L.; Torres, G.; Mugrauer, M.; Chen, W.P.; Hu, S.C.‐L.; Briceno, C.; Chini, R.; Bukowiecki, Ł.; Dimitrov, D.P.; Kjurkchieva, D.; et al.
Abstract With an apparent cluster diameter of 1.5° and an age of 4 Myr, Trumpler 37 is an ideal target for photometric monitoring of young stars as well as for the search of planetary transits, eclipsing binaries and other sources of variability. The YETI consortium has monitored Trumpler 37 throughout 2010 and 2011 to obtain a comprehensive view of variable phenomena in this region. In this first paper we present the cluster properties and membership determination as derived from an extensive investigation of the literature. We also compared the coordinate list to some YETI images. For 1872 stars we found literature data. Among them 774 have high probability of being member and 125 a medium probability. Based on infrared data we re‐calculate a cluster extinction of 0.9–1.2 mag. We can confirm the age and distance to be 3–5 Myr and870 pc. Stellar masses are determined from theoretical models and the mass function is fitted with a power‐law index of α = 1.90 (0.1–0.4 M⊙) and α = 1.12 (1–10 M⊙). (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)